Daoist and Confucianist Schools of Thought in Muslim-Majority Indonesian Society - Awangga, Panji Guniwa Aria; Truna, Dody S.; Albustomi, Ahmad Gibson (UIN Sunan Gunung Djati Bandung, 2024)
Confucianism is a school of thought that was born in China in the sixth century BC, founded by Confucius. This teaching emphasizes moral virtue, social relationships, and the connection between man and Heaven. The aim of this article is to explore the evolution of Confucianism from its early teachings to its more complex form of Neo-Confucianism, as well as its relevance in the modern context in China and East Asia. The methods used in this article involve a historical and philosophical approach through textual analysis of the teachings of Dao and Confucius, including the works of Zhu Xi, as well as a comparative study of its influence on culture, society, and politics in East Asia. The results of the analysis show that although Confucianism suffered a decline during the period of division after the fall of the Han Dynasty, its rise through Neo-Confucianism in the Song Dynasty era not only integrated metaphysical and spiritual elements but also strengthened education and self-development as the foundation of morality. In addition, the article reveals how Daoism and Confucianism have successfully adapted to modern challenges, such as interaction with Western thought and far-reaching social changes so that it remains relevant in shaping contemporary culture and ethics in East Asia.